A Study on the Waste Separation at Source and 3R Practice Among the Primary School Children in Muar District, Johor - LAAWANYA MANIMARAN, LAAWANYA MANIMARAN; Ts. Dr. ROSLINDA BINTI ALI, (Progress in Engineering Application and Technology, 2024)
Solid Waste Management (SWM) is a multifaced problem comprising political, socioeconomic, institutional, and environmental aspects. Due to exponential urban growth, it has become one of the most significant issues faced by urban spaces in developing countries. This research aims to investigate the role of education in influencing the waste separation and 3R behaviour of primary school children in Muar District, Johor.  Three selected primary schools in Muar are chosen to participate in this study.  A total of 480 questionnaires were distributed to the respondents and the results were analyzed by using the SPSS software. schools.  From the results, it can be said that there is a relationship between 3R-related activities conducted in school with students’ willingness to practice waste segregation and 3R in their daily lives. In addition, it can be concluded that female respondents are more likely to practice separation at source and 3R in their daily lives compared to male respondents. However, even though the understanding and awareness level of waste segregation and 3R practice among primary school students are considered relatively good, the students did not practice them in their everyday lives. One of the main reasons identified was the unavailability of the recycling bins.  According to the respondents, the unknown or inexistence of recycling bins in their housing area made them reluctant to practice 3R.